Against revolutions - James A. Secord; James Poskett (BJHS Themes)
The history of science in public discussion is dominated by large-scale narratives of revolution. These locate epistemic violence within specialist communities, obscuring the role of science in environmental destruction and in silencing other ways of engaging with the world. At the same time, the language of revolution has fostered an unrealistic image of science, giving too much prominence to crisis, heroic challenges to authority and the wholescale abandonment of established theory. Revolutionary narratives in history of science were consolidated in the decades around 1900, as the genealogy for an emerging union of science, industry and imperial power. Even when explicitly rejected, they function as ‘ghost narratives’ within teaching and research. Relocating epistemic violence not only involves changing the geography and chronology of established narratives, a project that is well under way. It also requires understanding that revolution is the wrong category of event for communicating science and its history.